ANALISIS PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA BADAN PERPUSTAKAAN DAERAH PROPINSI SUMATERA SELATAN - Ellen Sumiarni (JURNAL KOMPETITIF, 2014)
ABSTRACTThe objective of this research is to observe the impact of working situation ( X1 ) and working satisfaction ( X2 ) to employe performance ( Y ) of Regional Library Board Sout Sumatera Province..The population of this research is 73 employees of Regional Library Board South Sumatera Propince, Which 40 sample taken using proportional random sampling technique and another 18 sample for instrument sampling. Data collecting instrument using questioner with likert scale from various theory and form it into operation variable, which validity and reliable test taken to define the original of instrument. From inferential statistic analysis, correlation coefficient between working situation ( X 1 ) and employee performance variable ( X2 ) is 0.694, while 0.662 for correlation coefficient between working satisfaction variable ( X2 ) and employee performance variable ( Y ).Ã‚Â  Correlation coefficient between working situation variable ( X1 ) and working satisfaction ( X2 ) to employee performance is 0.9844, which show that there is a positive and strong relation. 0.713 determination coefficients means 71.3 % ofÃ‚Â  X1 and X2 variable form Y variable, result doubling linier regression: Y = 15.570 + 0.303X1 + 0.448X2 + E . On other word, empirically prove that employee performance improvement linier with improvement of working situation and satisfaction, partially or simultaneously.Ã‚Â Keywords: working situation, working satisfaction, employe performanceÃ‚Â